2022
DOI: 10.29036/jots.v13i24.374
|View full text |Cite
|
Sign up to set email alerts
|

Labour Migration and Tourism Flows: the Case of the EU

Abstract: During the last decades, the deepening of globalisation has led to an intensification of two forms of international human mobility – tourism and migration. Considering the high proportion of migrant workers in the tourism industry, migration’s possible negative or positive impact on international tourism comes to the forefront. The current article aims to explore the influence of migration, including labour migration, on tourism flows and the impact of tourism flows and migration on the labour market both in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Similar opinion presents also Novak et al (2016). However, inflow of cheap labour such as migration of foreign people causes decreases in wages (Přívarová et al, 2022). Since there is an increasing trend in a rising official migrant population in Slovakia (Přívara & Kiner, 2020), this fact might also affects unemployment rate of this country.…”
Section: Introductionmentioning
confidence: 69%
“…Similar opinion presents also Novak et al (2016). However, inflow of cheap labour such as migration of foreign people causes decreases in wages (Přívarová et al, 2022). Since there is an increasing trend in a rising official migrant population in Slovakia (Přívara & Kiner, 2020), this fact might also affects unemployment rate of this country.…”
Section: Introductionmentioning
confidence: 69%
“…Our findings contribute to the literature on tourism-led-migration, in a novel context of Croatia using micro-level data. While this question has been studied in different countries such as South Africa in Donaldson (2018) and across the EU in Přívarová et al (2022), this study investigates the within variation of localities across Croatia, one of the most tourism dependent countries in Europe. To that extent, our research is most similar to Ivandić (2021) who showed that tourism can be seen as a generator of demographic change, especially in rural and less developed areas.…”
Section: Discussionmentioning
confidence: 99%
“…Within the framework of social responsibility in the context of SMEs, publications mainly focus on employees (Alonso-Almeida et al, 2018), as the most important capital of any company. Nowadays, companies have difficulty finding an adequate workforce with the necessary competencies and experiences (Souto, 2022;Belas & Rahman, 2023), especially with the growing migration of the workforce (Privarova et al, 2022). From the above, we can conclude that retaining experienced employees is a key management task (Van Buren III, 2022;El-Kassar & Singh, 2019).…”
Section: Literature Reviewmentioning
confidence: 96%